Precise medical decision making in geriatric anti-depressant therapy. Issue 4 (3rd July 2016) - Gentile, Giovanna; Cipolla, Fabiola; Capi, Matilde; Simmaco, Maurizio; Lionetto, Luana; Borro, Marina
ABSTRACT: Introduction : Human aging is characterized by increasing vulnerability not only to diseases, but also to the treatments applied to that diseases. Geriatric depression is a frequent mental disorder often requiring pharmacological treatment, which commonly is added to other medications taken to treat chronic or acute co-morbidities. The challenges of appropriate treatment of elderly are increasingly recognized as an urgent health problem. Areas c overed : The challenges of appropriate geriatric anti-depressant prescription, and the role of novel tools developed by Precision Medicine. The data were obtained searching in MEDLINE: pharmacokinetics, pharmacodynamics, pharmacogenetics, antidepressants, drug-drug interactions and elderly, in the period 1994–2016. Expert c ommentary : The Precision Medicine approach take advantage by novel decision-supporting tools, as pharmacogenomic testing, drug-drug interactions evaluation and therapeutic drug monitoring, allowing to improve informed-decision making in prescription of antidepressants.